Oxygen saturation in patients during hemodialysis at different altitudes - Rosales-Mendoza, Karina (2021)
Introduction Patients undergoing hemodialysis may develop hypoxemia during the procedure, and hypoxemia may become more intense if hemodialysis is performed in a high altitude environment. Objectives To assess variations in oxygen saturation in patients undergoing hemodialysis at different altitude levels. Material and methods This is a prospective case series, where patients from hemodialysis programs in three cities were assessed. These places were at 101-, 2335-, and 3825- meters above sea level. Patients had their oxygen saturation measured in a semi-sitting position with a pulse oxymeter device. Measurements were taken before, during, and at the end of hemodialysis sessions. Results Sixty-five patients undergoing hemodialysis were included. They were from three cities at different altitude above sea level. Oxygen saturation significantly decreased as long as altitude increased (97,32 ± 1,10 vs. 94,75 ± 2,17 vs. 84,85 ± 5,86 p= 0,00). Oxygen saturation showed changes before, during, and at the end of hemodialysis procedures at different altitude. Ferritin levels were lower in high altitude patients compared with those at sea level and at moderate altitude (131,75 [106,04 – 157,45] vs. 493,38 [273,19 – 713,56] vs. 550,66 [329,75-771,57] p=0,01). Hemoglobin values were lower in patients from middle altitude levels (10,8 [10,12-11,47] vs 11,32 [10,79-11,85] vs 11,84 [11,54-12,14] p=0,03) Conclusions In patients undergoing chronic hemodialysis oxygen saturation is reduced as long as altitude increases, and significant variations were found during hemodialysis procedures.